Islamic Republic of Iran : Selected Issues Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This Selected Issues paper analyzes economic growth in Iran. It uses a growth-accounting exercise to quantify the historical sources of growth over 1960-2002, including human capital accumulation and the contribution of Total Factor Productivity to growth. The paper presents an empirical study to quantify the role of several other contributing factors commonly discussed in the cross-country growth literature, including macroeconomic stability, financial development, trade openness, and the change in the terms of trade. The paper also examines issues in medium-term management of oil wealth in Iran.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet